A dynamically turbo-charged heuristic for graph coloring. (c2018) - Chahine, Bachir (2018)
We launch a study on the dynamic form of the graph coloring problem proving it to be fixed-parameter tractable with respect to the edit-parameter. This leads us to present a new turbo-charged heuristic for the problem that works by merging standard heuristic tools like Greedy coloring with the turbo-charging technique. The recently introduced turbo-charging idea is further enhanced in this thesis by introducing a dynamic version of turbo-charging where the moment of regret and the rollback points are determined dynamically. Experiments comparing our turbo-charging algorithm to other heuristics were conducted on a number of known benchmarks. Our heuristic produced exceptional results that were often better than all the other available heuristics. Keywords: